Complex Systems and Fractional Dynamics - António M. Lopes; J. A. Tenreiro Machado (Entropy, 2018)
Complex systems (CS) are pervasive in many areas of science and technology, namely in financialmarkets, transportation, telecommunication and social networks, world and country economies,immunological systems, living organisms, computational systems, and electrical and mechanicalstructures [...]